(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This study included the definition of overcrowding in traditional settlements, confinement of animals and not going out to graze in natural pastures, which causes stress and its impact on the characteristics and standards in the blood. Metabolism for two weeks by oral dosing of 3 g, 6 g and control group, and we found that the best use of a concentration of 3 g gives good results for adaptation and changes the number of white blood cells, as there was a significant increase in stressed animals when adding vitamin C, and the variation decreased significantly(p < 0.05) for the lymphocytes and the value of granulocytes increased, Significant(p < 0.05) differences were found between the values, and the number of granulocytes, lymphocytes in a good measure to indicate changes caused by environmental stress, overcrowding, and there is a significant increase in the values number of red blood cells, and that vitamin C will enhance immunity and the ability to resist and adaptation.